Instrumental support: A conceptual analysis. Issue 4 (8th February 2022) - Schultz, Beth E.; Corbett, Cynthia F.; Hughes, Ronda G.
Abstract: The aim of this paper was to use the Walker and Avant method of concept analysis to evaluate the concept of instrumental support in the context of hospital to home care transitions. Findings from this concept analysis suggest three defining attributes of instrumental support: informal support providers, tangible support, and unmet personal needs. Antecedents identified: a strong and supportive social network, an independently functioning adult, an illness resulting in hospitalization, a change in functional status, and the patient being discharged home from the hospital. Consequences of not having adequate instrumental support: unsuccessful recovery at home, increased risk for hospital readmission, decline in physical functioning, health complications, and increased risk of mortality. Empirical referents: patient's report of successful recovery, returning to an independent level of functioning, and the lack of hospital readmission or health complication. A model and a contrary case study were developed to provide examples of clinical cases related to instrumental support. Recommendations related to clinical practice include evaluating the availability/adequacy of instrumental support before hospital discharge and including the identified instrumental support person in the discharge planning process. There are proven benefits of having people within one's social network providing instrumental support during the home recovery period.